The Controversy of Understanding Wahdatul Hamzah Fansuri Mufti in The Sultanate of Aceh - Kasmuri Selamat; Wiza Atholla Andriansyah; Khotimah Khotimah; Abd. Ghofur; Deswita Deswita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Hamzah Fansuri was a Sufi figure, writer and Mufti in the Sultanate of Aceh Darussalam during the time of Sultan Alaudin Riayat Syah (1596-1604). The controversy about his thoughts is one of the reasons for the interest in this article. The interesting thing about his thoughts is about wahdatul wujud. At first glance, this thought is normal, but the interesting thing is the understanding that was developed in the process of Islamization in the archipelago when the two schools of Sufism, Sunni and Shia, met. Therefore, this article will discover this side of the controversy and of course its influence on the development of Sufism in Indonesia. Data obtained from library research. The data analysis technique was carried out using qualitative analysis techniques in a deductive manner. The results of this study show that the controversy over Hamzah Fansuri's thoughts about Wahdatul wujud is a Sufi concept that was influenced by the thoughts of previous Sufi figures such as Ibn Arabi and Al-Qunawi. Its influence on the development of Sufism in Indonesia lies in the understanding of Wahdatul Wujud, understood as a single form which is the ultimate reality. Being other than Allah are shadows or manifestations of a single being. Hamzah Fansuri understands that the essence of existence is only one, namely Allah SWT and everything is explained in metaphorical language.